Analisis Perkembangan Bahasa Anak Sindrom Down (Studi Kasus di Kota Parepare) - Novita Ashari; Nurazizah Nurazizah; Ummi Rahayu; Nurul Nisya; Harpina Harpina; Riska Febrianti; Suryanita Zyaniah (Universitas Negeri Malang, 2023)
Down syndrome children experience slower language development due to anatomical differences and otitis media or infection of the middle ear. Language development barriers in children can occur in two forms. This study aims to analyze the language development of children with Down syndrome. The method used in this research is a qualitative research method with a case study approach model. The data collection techniques used in this research include interview, observation, and documentation techniques. This research was conducted in the Small Industry of Parepare City. The subject of this research was FJ who is eight years old with down syndrome. This study shows the results that of the nine indicators of speech and language development of eight-year-old children, FJ has not been able to tell funny stories and riddles to others, FJ has not been able to carry out orders and often asks for repetition of words, FJ has not known the reading that was shown but FJ was able to repeat the reading that was thrown by the researcher, FJ has not been able to write and send letters correctly, FJ has not been able to capture a vocabulary when communicating, FJ rarely responds to praise or criticism to others because FJ is lacking in communication, FJ has not been able to write letters with dotted lines, FJ has not understood code language such as the shape of a butterfly, and FJ has not been able to communicate fluently.Anak down sindrom mengalami perkembangan bahasa lebih lambat karena perbedaan anatomi dan otitis media atau infeksi pada bagian tengah telinga. Metode yang digunakan dalam penelitian ini berupa metode penelitian kualitatif dengan model pendekatan studi kasus. Teknik pengumpulan data yang digunakan dalam penelitian ini meliputi teknik wawancara, observasi, dan dokumentasi. Penelitian ini dilakukan di Industri Kecil Kota Parepare. Penelitian ini menunjukkan hasil bahwa FJ belum mampu melontarkan cerita lucu dan teka-teki kepada orang lain, FJ belum mampu melaksanakan perintah dan sering meminta pengulangan kata, FJ belum mengetahui bacaan yang diperlihatkan namun FJ mampu mengulang bacaan yang dilontarkan oleh peneliti, FJ belum mampu menulis dan mengirim surat dengan tepat, FJ belum mampu menangkap suatu kosakata saat berkomunikasi, FJ jarang memberi respon pujian atau kritikan kepada orang lain, FJ belum mampu menulis huruf dengan garis putus-putus, FJ belum memahami bahasa kode seperti bentuk kupu-kupu, dan FJ belum mampu berkomunikasi dengan lancar.